Crystallisation and dissolution studies of struvite in aqueous solutions - Ariyanto, Eko (Curtin University, 2013)
Struvite (MgNH4PO4.6H2O) is present in municipal wastewater treatment plants. It causes scaling in the plant but recent studies showed that it could be recovered as an alternative form of fertilizer. This study was conducted in order to get a better understanding of the crystallisation of struvite. The results may be used for better design and operation of wastewater treatment plants with production of struvite as a useful by-product.